Galantamine ameliorates hyperoxia-induced brain injury in neonatal mice - Zaghloul, Nahla; Cohen, Naomi S.; Ayasolla, Kamesh R.; Li, Hsiu-Ling; Kurepa, Dalibor; Ahmed, Mohamed N. (Frontiers in Neuroscience, 2023)
Prolonged oxygen therapy in preterm infants often leads to cognitive impairment. Hyperoxia leads to excess free radical production with subsequent inflammation, astrogliosis, microgliosis and apoptosis. We hypothesized that Galantamine, an acetyl choline esterase inhibitor and an FDA approved treatment of Alzheimer’s disease, will reduce hyperoxic brain injury in neonatal mice and will improve learning and memory. Mouse pups at postnatal day 1 (P1) were placed in a hyperoxia chamber (FiO2 95%) for 7 days. Pups were injected daily with Galantamine (5mg/kg/dose) or saline for 7 days. Hyperoxia caused significant neurodegeneration in cholinergic nuclei of the basal forebrain cholinergic system (BFCS), laterodorsal tegmental (LDT) nucleus and nucleus amibiguus (NA). Galantamine ameliorated this neuronal loss. Treated hyperoxic group showed a significant increase of choline acetyl transferase (ChAT) expression and a decrease of acetyl choline esterase activity, thus increasing acetyl choline levels in hyperoxia environment. Hyperoxia increased pro-inflammatory cytokines namely IL -1β, IL-6 and TNF a, HMGB1, NF-B activation. Galantamine showed its potent anti-inflammatory effect, by blunting cytokines surges among treated group. Treatment with Galantamine increased myelination while reducing apoptosis, microgliosis, astrogliosis and ROS production. Long term neurobehavioral outcomes at P60 showed improved locomotor activity, coordination, learning and memory, along with increased hippocampal volumes on MRI with Galantamine treated versus non treated hyperoxia group. Together our findings suggest a potential therapeutic role for Galantamine in attenuating hyperoxia-induced brain injury.